Analyzing the impact of in-rack sprinklers in a warehouse fire: A demonstration of the role optimization has in mitigating damage. (April 2015) - Trapp, Andrew C.; Rangwala, Ali S.
Abstract: This study presents a tool that illustrates the potential and role that optimization can have in fire protection design and performance. Specifically, the tool uses validated engineering correlations to simulate a warehouse fire, and evaluates whether it is controlled by modeling the placement and number of sprinklers – both in-rack and ceiling. Using initial model inputs that include storage configuration, commodity type, water supply, and sprinkler type, we allow a fire to ignite and simulate its growth behavior and corresponding effects on a nearby target array. For any initial set of input parameters, our tool demonstrates the minimum number and location of available in-rack sprinklers to control the flame spread. With reasonable run times, our work yields new insights into the design of sprinkler systems and, more broadly, the usefulness of optimization in fire protection design. Highlights: Simulate industrial warehouse fire and its interaction with sprinkler system. Account for storage configuration, commodity type, water supply, and sprinkler type. Determine minimal configuration (number and placement) of sprinklers for fire control. Highlight that fire control can be completely dependent on sprinkler configuration. Demonstrate potential and role optimization has in this and other hazardous settings.